1997
DOI: 10.1111/j.1365-2621.1997.tb15450.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Previous Thermal Treatment of Chicken Patties by Visible/Near‐Infrared Spectroscopy

Abstract: Cooking history at the center point in chicken patties was quantified in terms of both time-temperature integrated indices (C and F) and endpoint temperature (T max ). Intact cooked patties were scanned for reflectance and transmittance spectroscopy. Reflectance resulted in better calibrations for the indices of thermal history than did transmittance. Three reflectance wavelength ranges, visible (400 to 700 nm), near-infrared (1100 to 2500 nm), and visible/near-infrared (400 to 2500 nm), were evaluated, and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…The relationships between the data logger and NIR spectroscopy predicted parameters (r) were high (r > 0:90). This result is in good agreement with that reported by Chen and Marks (1997) for chicken patties.…”
Section: Evaluation Of Treatment Parameterssupporting
confidence: 95%
See 1 more Smart Citation
“…The relationships between the data logger and NIR spectroscopy predicted parameters (r) were high (r > 0:90). This result is in good agreement with that reported by Chen and Marks (1997) for chicken patties.…”
Section: Evaluation Of Treatment Parameterssupporting
confidence: 95%
“…Chen and Marks (1997) reported no linear relationships between spectral data and F values and reported that base-10 logarithms had the best linear relationship with spectral data. As a result, the F values were first transformed to base-10 logarithms.…”
Section: Evaluation Of Treatment Parametersmentioning
confidence: 95%
“…5 shows the second derivative of the visible spectra of chicken meats cooked at a constant air temperature of 150 C for 3, 6, 9, and 18 min. With cooking, extensive changes in the appearance and physical properties of meats occur (Chen & Marks, 1997Kinsman et al, 1994;Swatland, 1983). These changes include the toughening and discoloration of the meats, with toughening due to the denaturation of proteins and discoloration due to the oxidization of pigment heme groups (Kinsman et al, 1994).…”
Section: Visible Spectra Of Cooked Chicken Meatsmentioning
confidence: 99%
“…The applications include the quantitative prediction of the physical characteristics of heat-treated chicken patties (Chen & Marks, 1997, the identification of the chicken species from other meats (McElhinney et al 1999;Rannou & Downey, 1997), the discrimination of ''slow-growing'' chickens from ''industrial'' ones (Fumiere et al, 2000), and the classification of chicken carcasses into wholesome and unwholesome classes at the slaughter plant (Chen et al, 1996.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation